Pengaruh Desentralisasi Fiskal terhadap Pertumbuhan Ekonomi Kota Ambon - Jani, Jani; Matdoan, Arsad; Payapo, Rukmuin Wilda; Louhenpessy, Fredy Hendry (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2025)
This research aims to determine the effect of fiscal decentralization on economic growth in Ambon City. Ambon City has implemented fiscal decentralization, but its economic development is still lagging behind other regions in Indonesia. Qualitative and quantitative analysis was used, with the results showing an average increase in the level of fiscal decentralization of 14% over 10 years (2014-2023) which had a significant effect on Regional Original Income (PAD) and government financial performance. Meanwhile, Ambon City's economic growth as measured by Real GRDP experienced an average increase of 4.57% in the same period. The effect of fiscal decentralization on economic growth reached 94.2%, showing a strong and positive relationship. Therefore, the Ambon City government needs to intensify existing sources of income, or extensify existing sources by utilizing the economic potential in Ambon City so that PAD continues to increase without burdening the community's economy and implement decentralization policies. maximal fiscal capacity, so that economic growth in Ambon City can increase from year to year.